Regional cooperation for improving agriculture production efficiency: A strategic tool for emission reduction - Kazi Arif Uz Zaman (Asian Development Bank Institute (ADBI), 2022)
The growing population and climatic uncertainties have compelled producers to undertake faster exploitation of the resources in agricultural production to meet global food security, which, in turn, leads towards unsustainable and input-led inefficient production growth. The problem is further exacerbated by the increasing emission of GHGs from this production process. This paper suggests a solution to this by advocating the role of regional cooperation to increase the technical efficiency level in the agricultural production of countries through technology transfer, knowledge sharing, capacity building, and adequate investment under the regional cooperation framework. Concurrently, this study links this improvement of production efficiency with the reduction of emissions both theoretically and empirically for all Asian subregions. This paper first adopts the stochastic frontier model-a widely used statistical technique that frames the production functions while estimating the inefficiencies of economic units. Using 2010-2016 panel data on agriculture production and five inputs-land, labor, capital, fertilizer, and energy-this paper estimates the agriculture production efficiencies of the countries under five Asian subregions. Estimations reveal that West Asia, Southeast Asia, South Asia, East Asia, and Central Asia have agriculture production efficiencies of 70%, 85%, 66%, 92%, and 76%, respectively. Following the estimations and other calculations, this study reveals that with concerted efforts towards optimizing production efficiencies under (sub)regional cooperation frameworks, an annual emission of 384.5 megatons of CO2eq GHG could have been reduced in Asia while keeping the production at the current level. The potential reduction of emissions equals 16.8% of Asia's total emissions originating from agricultural activities and 7.1% of that of global emissions.
Keywords: R11; F53; O47; O53; Q15; Q56; 330; agriculture production efficiency; regional cooperation; stochastic frontier model; emission reduction; Asian subregions